Sentiment Analysis About Acquisition and Policy of X (Twitter) by Elon Musk - Fatimatuzzahro, Adelia; Larasati, Aisyah; Dwiastuti, Anik (Universitas Negeri Padang, 2025)
Social media Twitter (now X) is quite popular because it offers the ability to communicate between users and accelerate the flow of information obtained. In its development, the acquisition of the company by Elon Musk led to various changes. Some of the new policies had a direct impact on users and caused mixed reactions. This research applies a comparison between the two types of labeling techniques using TextBlob and VADER, a comparison of algorithms using Random Forest and Balanced Random Forest, as well as the use of algorithm parameters by default and Grid Search, to find information on user perceptions of the impact of the acquisition and new policy X by conducting sentiment analysis. The data used is the result of crawling X's post in the period from the emergence of the acquisition issue until the rebranding of the Twitter name and logo to X, namely April 25, 2022 to July 23, 2023. The results show that visually, these three factors have an accuracy level that shows the use of superior factors, namely TextBlob, Balanced Random Forest, and default parameters, whose combination obtained the highest accuracy value of 87%. The results of sentiment classification using two labeling techniques show that positive sentiment is greater than negative sentiment. However, in negative sentiment there are several problems based on the highest frequency of words that appear. So in this study, several recommendations are given that can be done to meet the expectations of user satisfaction with the X platform.